Analysis of microbial community diversity of Pingba Baijiu Xiaoqu by single molecule real-time sequencing technology - ZHOU Tingting, HU Yuedan, HU Zhaomei, HUANG Wei (Zhongguo niangzao)
In this study, the microbial community diversity of Pingba Baijiu Xiaoqu was analyzed by single molecule real-time sequencing (SMRT). The results showed that the Chao1, Shannon, InvSimpson indexes were 507, 4.58 and 6.06, respectively, indicating that the composition and structure of microbial community in Pingba Baijiu Xiaoqu were relatively complex. The microbial communities were mainly composed of molds, followed by bacteria, and the relative abundance of yeasts were relatively low. The relative abundance of bacteria in the top 15 microorganisms in Pingba Baijiu Xiaoqu was the highest (38.73% at genus level and 40.39% at species level), which was much higher than that of yeasts and molds. The dominant bacteria were Weissella cibaria, Weissella confusa and Bacillus cereus, the dominant molds were Rhizopus oryzae, Rhizopus microsporus and Lichtheimia ramosa, and the dominant yeasts were Saccharomyces cerevisiae and Saccharomycopsis fibuligera.